Nonclinical safety testing of human pharmaceuticals in relation to clinical development - van der Laan, Jan Willem (Henry Stewart Talks, 2026)
ICH participants and ICH safety topics, Benefit-risk assessment, ICH M3: Mother of all guidelines, Guidance history on first-in-human (FIH) starting dose, ICH S7A: Safety pharmacology studies, S7B: Non-clinical testing strategy, Genotoxicity testing, ICH S4: Single and repeated dose toxicity studies